Long Noncoding RNA FGFR3-AS1 Promotes Hepatocellular Carcinoma Carcinogenesis via Modulating the PI3K/AKT Pathway - Zhuang, Juhua (Oncol Res, 2018)
Hepatocellular carcinoma (HCC) as one of the most refractory cancers leads to high mortality worldwide. Long noncoding RNAs have been widely acknowledged as important biomarkers and therapeutic targets in HCC. In this study, we investigated the effects of long noncoding RNA FGFR3-AS1 on tumor growth and metastasis in HCC. First, we found that the expression of FGFR3-AS1 was upregulated about threefold in HCC samples and cell lines. We knocked down FGFR3-AS1 in Huh7 and Hep3B cells and found that FGFR3-AS1 knockdown significantly inhibited cell proliferation but induced apoptosis. Moreover, FGFR3-AS1 knockdown led to more HCC cells arrested in the G(0) stage. FGFR3-AS1 knockdown significantly inhibited cell migration and invasion. Additionally, we found that FGFR3-AS1 silencing dramatically delayed tumor growth in vivo. We found that, mechanistically, FGFR3-AS1 silencing decreased the activation of the PI3K/AKT signaling pathway. Taken together, our data demonstrated the pro-oncogenic role of FGFR3-AS1 in HCC and suggested that FGFR3-AS1 may serve as a novel biomarker for the diagnosis and therapeutic target for HCC treatment.